Intraoral spindle-cell lipoma: report of a case and literature review. - Khoo, S.P.; Lian, C.B. (1995)
Spindle-cell lipoma (SCL) of the oral cavity is very rare. There are only four such reported cases in the literature. A concise literature review of SCL and a case report of a SCL affecting the cheek and lip of a 23-year-old man is presented.